ROBOSTAN : Robot Penyemprot Disinfektan Pada Lantai Masjid Secara Otomatis - Firdaus Firdaus; Affan Rambe Mahmud; Anjar Rohmiati Anggi (UII, 2020)
Corona Virus Disease 19 or better known as COVID-19 began to enter Indonesia in mid-2020. As reported by WHO via detik.com, the incidence of death due to COVID-19 in Indonesia is about 0.34 per 100,000 population, or 3.4 percent. %. This indicates that the disease has infected so many populations in various countries and is very dangerous. This condition worries and worries the community. On the other hand, the attitude of the people to come to the mosque is very enthusiastic. The mosque is the most visited place of worship at certain times. This is because the function of the mosque is very significant to human life, namely as a center of worship, social, da'wah, education, politics, economy, culture, and civilization. Mosque floors and prayer mats are one of the media that have the potential to spread the Coronavirus. Coronavirus transmission can be through objects contaminated with the virus. The virus carried by previous congregations can stick to the floor and potentially be inhaled by other congregations while performing prostration movements in prayer. It is necessary to spray disinfectant on the floor and carpet of the mosque to prevent the spread and transmission of COVID-19. Therefore, in this final project, we created a technology to be able to help the process of sterilizing the mosque floor automatically. The technology we created is in the form of a robot that can spray disinfectant automatically onto the floor of the mosque. This robot uses a power supply in the form of a battery, and uses 4 sensors, namely infrared sensor e18-d80nk located on the right and left of the robot wheel, next to it is also located rotary encoder sensor, gyro sensor mpu6050 located in the middle and infrared obstacle sensor located below the robot. The design of this robot has been tested in the form of an experiment. From the experiment results, the robot can walk and spray the disinfectant liquid well using blue light sterilization, so that the liquid is sprayed in the form of fine grains so as not to cause the floor to become wet.